2014
DOI: 10.1508/cytologia.79.161
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Effects of Crude Extracts of <i>Peganum harmala</i> Seeds and Their Effects on <i>Vicia faba</i> Plants

Abstract: SummaryThe present study evaluates the genotoxic and cytotoxic effects of the crude water and ethanol extracts of Peganum harmala L. (Zygophyllaceae) on the Vicia faba L. M1 generation. Two types of treatments were carried out in this study. In the first type, the germinated root tips were treated with four dilutions of the water extract and ethanol extract (12.5, 25, 50 and 100%). All concentrations were applied for 3, 6, 12 and 24 h. In the second treatment, soaked V. faba seeds were treated with the same co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous studies reported that the cell division during growth was widely affected by several stress conditions (Firbas and Amon, 2013;Mekki, 2014;Souguir et al, 2011). Under salt stress (40-160 mM), decreases in mitotic index inducing growth inhibition were also investigated in Allium cepa roots (Teerarak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the cell division during growth was widely affected by several stress conditions (Firbas and Amon, 2013;Mekki, 2014;Souguir et al, 2011). Under salt stress (40-160 mM), decreases in mitotic index inducing growth inhibition were also investigated in Allium cepa roots (Teerarak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is also believed to have been mentioned in the Persian ancient cultures as Avestan haoma (Monsef et al, 2004;Mekki, 2014). It has been claimed to have habitats in Nord Africa Sahara regions, in Eastern countries including Iran, Iraq, Turkey, China, and Pakistan, and in the Mediterranean regions across Europe (Spain, Italy) (Monsef et al, 2004;Mekki, 2014). Other species of the genus include Peganum mexicanum originating from Mexico, Peganum nigellastrum and Peganum multisectum whose first specimens were discovered in Mongola, China, and Peganum taxanum endemic to Southern North America.…”
Section: The Genus Peganummentioning
confidence: 97%
“…The most popular species in the group, Peganum harmala, originates from the Mediterranean region, Southeastern Europe. It is also believed to have been mentioned in the Persian ancient cultures as Avestan haoma (Monsef et al, 2004;Mekki, 2014). It has been claimed to have habitats in Nord Africa Sahara regions, in Eastern countries including Iran, Iraq, Turkey, China, and Pakistan, and in the Mediterranean regions across Europe (Spain, Italy) (Monsef et al, 2004;Mekki, 2014).…”
Section: The Genus Peganummentioning
confidence: 99%
“…The aquatic extracts were done from the aerial parts of Sinai's flora P. harmala, A. fragrantissima and T. hirsuta according to Al-Mizrakchi (1998). The stock solutions of the aqueous extracts as well as the different concentrations (5, 10 and 15%) were preparedin August 2018, according to the method described by Abdel-Salam et al (2009) and Mekki (2014).…”
Section: Extract Preparationmentioning
confidence: 99%
“…Recently, many studies indicated that, many wild plant extracts are natural sources of many products and has stimulatory effects on bean plants. Mekki (2014) studied cytogenetic effects of crude extracts of Peganum harmala and their effects on Vicia faba plants and found that the highest concentration of ethanol extract resulted in the lowest MI and the highest values of plant height and the number of branches per plant. Contrarily, shoo et al (2013) found that application of aqueous extract of whole P. harmala plant greatly suppressed growth of wheat and lettuce seedling, (Shao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%